Evaluasi Program Pagi Mengaji dan Tahfidz (Pantadz) di SMPN 3 Narmada - Ruslan Zain; Abdul Kadir Jaelani (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Education plays a strategic role in shaping students’ character and personality, particularly at the junior high school level, which represents a transitional phase marked by identity formation. At this stage, students are vulnerable to various environmental influences, making systematic efforts necessary to instill moral, ethical, and religious values. One strategy that schools can implement to address this need is the integration of religious activities as a means of habituation and character reinforcement. SMPN 3 Narmada responded to this need by implementing the Morning Qur’an Recitation and Tahfidz Program (Pantadz), conducted every morning for 20 minutes. The program includes Qur’an recitation activities on Tuesdays, Wednesdays, and Thursdays, as well as tahfidz activities on Fridays, and involves all students from grades VII to IX. The implementation of this program was based on findings from Islamic Education teachers and classroom teachers indicating that some students had not yet achieved fluency in reading the Qur’an. In addition, data from Guidance and Counseling teachers revealed character and moral issues among a number of students. This study aims to evaluate the effectiveness of the Pantadz program in shaping students’ character. The research focuses on the influence of morning Qur’an recitation activities on character development, the implementation process, the character aspects that develop, supporting and inhibiting factors, and the long-term impact on students’ spiritual intelligence and social interactions. The findings of this study are expected to provide recommendations for schools to improve the quality and sustainability of the Pantadz program in a more effective and holistic manner.